Pengaruh Supervisi Akademik Kepala Sekolah dan Budaya Sekolah Terhadap Mutu Mengajar Guru - Nursidah Nursidah; Muh Yunus; Elpisah Elpisah (Jurnal Pendidikan Ekonomi (JUPE), 2022)
The purpose of this study was to determine 1) The effect of the principal's academic supervision and school culture simultaneously on the quality of teacher teaching, 2) The influence of the principal's academic supervision on the teaching quality of teachers, 3) The influence of school culture on the teaching quality of teachers at SMAN 6 Wajo. This research is a quantitative descriptive research, the population is all teachers of SMAN 6 Wajo. The sample is 54 people. The results of the study show 1) There is a simultaneous influence of the principal's academic supervision and school culture on the teaching quality of teachers, where the principal's supervision indicators are in the good category, while school culture and teacher teaching quality descriptively are in the very good category, 2) There is an influence The principal's academic supervision on the teaching quality of teachers, where the principal's academic supervision has a significant effect on the teaching quality of teachers, it means that the better the principal's academic supervision, the better the teacher's teaching quality, 3) There is an influence of school culture on the teaching quality of teachers at SMAN 6 Wajo where school culture has a significant effect on the quality of teacher teaching, meaning that the better or conducive school culture, the better the teaching quality of teachers.